2005
DOI: 10.1136/bmj.38576.494363.e0
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal exposure to betamethasone: psychological functioning and health related quality of life 31 years after inclusion in randomised controlled trial

Abstract: Objectives To determine if antenatal exposure to betamethasone for the prevention of neonatal respiratory distress syndrome alters psychological functioning and health related quality of life in adulthood. Design Follow-up of the first and largest double blind, placebo controlled, randomised trial of a single course of antenatal betamethasone for the prevention of neonatal respiratory distress syndrome. Setting Tertiary obstetric hospital in Auckland, New Zealand. Participants 192 adult offspring, mean age 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
4
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 19 publications
2
101
4
8
Order By: Relevance
“…NBW control participants). Although our findings appear to be at odds with the results of randomized controlled trials of people exposed to ACS or placebo, 24,25 those studies contained 31 and so our findings must be replicated.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…NBW control participants). Although our findings appear to be at odds with the results of randomized controlled trials of people exposed to ACS or placebo, 24,25 those studies contained 31 and so our findings must be replicated.…”
Section: Discussioncontrasting
confidence: 60%
“…21 Although observational studies suggest that fetal exposure to repeated courses of ACS is associated with an elevated risk of ADHD symptoms in childhood, 22,23 randomized controlled trials of ACS have not linked antenatal steroid exposure to mental health problems in the third or fourth decades of life. 24,25 However, these studies contained very few ELBW infants, had high rates of attrition, and relied on self-report questionnaires to ascertain psychiatric outcomes, making it difficult to generalize their findings to those born at ELBW.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that exposure to antenatal betamethasone did not alter SES, psychological functioning, or HRQoL in this cohort. 13 The aim of the present study was to determine the affect of preterm birth on SES, cognitive functioning, working memory and attention, psychiatric morbidity, handedness, and HRQoL at 31 years of age.…”
mentioning
confidence: 99%
“…Preterm infants benefit from administration of antenatal steroids to the mother prior to birth, which reduces neonatal mortality and severe neonatal morbidity in regard to conditions such as respiratory distress and intraventricular hemorrhage [32,33]. In addition to the challenges posed by preterm birth, intensive care in itself can be quite stressful.…”
Section: The Preterm Infantmentioning
confidence: 99%